Comprehensive Analysis of the Therapeutic IgG4 Antibody Pembrolizumab: Hinge Modification Blocks Half Molecule Exchange In Vitro and In Vivo. Issue 12 (26th August 2015) - Yang, Xiaoyu; Wang, Fengqiang; Zhang, Ying; Wang, Larry; Antonenko, Svetlana; Zhang, Shuli; Zhang, Yi Wei; Tabrizifard, Mohammad; Ermakov, Grigori; Wiswell, Derek; Beaumont, Maribel; Liu, Liming; et al.
Abstract : IgG4 antibodies are evolving as an important class of cancer immunotherapies. However, human IgG4 can undergo Fab arm (half molecule) exchange with other IgG4 molecules in vivo . The hinge modification by a point mutation (S228P) prevents half molecule exchange of IgG4. However, the experimental confirmation is still expected by regulatory agencies. Here, we report for the first time the extensive analysis of half molecule exchange for a hinge‐modified therapeutic IgG4 molecule, pembrolizumab (Keytruda) targeting programmed death 1 (PD1) receptor that was approved for advanced melanoma. Studies were performed in buffer or human serum using multiple exchange partners including natalizumab (Tysabri) and human IgG4 pool. Formation of bispecific antibodies was monitored by fluorescence resonance energy transfer, exchange with Fc fragments, mixed mode chromatography, immunoassays, and liquid chromatography–mass spectrometry. The half molecule exchange was also examined in vivo in SCID (severe combined immunodeficiency) mice. Both in vitro and in vivo results indicate that the hinge modification in pembrolizumab prevented half molecule exchange, whereas the unmodified counterpart anti‐PD1 wt showed active exchange activity with other IgG4 antibodies or self‐exchange activity with its own molecules. Our work, as an example expected for meeting regulatory requirements, contributes to establish without ambiguity that hinge‐modified IgG4 antibodies are suitable for biotherapeutic applications. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4002–4014, 2015